1990
DOI: 10.1093/protein/4.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between stability of a protein and its dipeptide composition: a novel approach for predicting in vivo stability of a protein from its primary sequence

Abstract: Statistical analysis of 12 unstable and 32 stable proteins revealed that there are certain dipeptides, the occurrence of which is significantly different in the unstable proteins compared with those in the stable ones. Based on the impact of these dipeptides on the unstable proteins over the stable ones, a weight value of instability is assigned to each of the dipeptides. For a given protein the summation of these weight values normalized to the length of its sequence helps to distinguish between unstable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
664
0
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,074 publications
(721 citation statements)
references
References 0 publications
11
664
0
7
Order By: Relevance
“…The instability index and grand average of hydropathicity (GRAVY) were estimated following the method of Guruprasad et al (1990) and Kyte and Doolittle (1982), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The instability index and grand average of hydropathicity (GRAVY) were estimated following the method of Guruprasad et al (1990) and Kyte and Doolittle (1982), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of purified protein in the sample is evaluated from the value of extinction coefficient (Umang et al, 2012). The stability of protein is calculated from its instability index (II) and the proteins are predicted as stable when their instability index is smaller than 40; however when the value of instability index is greater than 40, the protein is regarded as unstable (Guruprasad et al, 1990). The volume occupied by aliphatic amino acids side chain (alanine, valine, leucine and isoleucine) relative to total volume occupied is called aliphatic index and it determines the thermostability of a globular protein (Walker, 2005).The hydrophilicity or hydrophobicity of protein is determined by grand average of hydropathicity (GRAVY), which is the ratio of sum of hydropathy values of all the amino acids to total number of residues in the sequence (Umang et al, 2012).…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…Only the analysis of the instability index (II) showed a difference, and we found that ala310 had an II value of 39.08, suggesting that the protein is stable, and instead ser310 had a value of 40.26, suggesting protein instability. 12 To investigate the role of this polymorphism in schizophrenia we have analysed in a case-control association study the allele frequencies and the genotype distributions in a population of 99 schizophrenic patients and 116 unaffected controls. Allele frequencies, genotype distributions and the statistical analysis are shown in Table 1.…”
mentioning
confidence: 99%